Sosialisasi Sumur Resapan dan Bioswale Upaya Meminimalisir Genangan di Desa Arisan Buntal, Kayu Agung, Sumatera Selatan - Pingkan Nuryanti; Bambang Sulistyantara; Gemilia Elvarino (Institut Pertanian Bogor, 2023)
Arisan Buntal Village is one of the villages in Kayu Agung District, Ogan Komering Ilir Regency, with a village area of 2.7 km2. Arisan Buntal village is often flooded due to the construction of the Lampung-Palembang toll road. One solution that can be applied to overcome this problem is the application of infiltration wells and bioswales in residents' yard parks. This activity aims to share knowledge about infiltration wells and bioswales with the community so that people can apply it in their respective yards. The methods used in this activity are partner exploration, construction stages and dissemination. The results of planting development equipped with infiltration wells and bioswales effectively reduce puddles in the house's yard when it rains. During dissemination, the community was very enthusiastic about listening to the material. From the results of the post-test community, the community initiated that the activities of lecturers returning home succeeded in increasing community knowledge.